2021
DOI: 10.1177/21582440211061573
|View full text |Cite
|
Sign up to set email alerts
|

“Behind the Façade: Motivations for Cosmetic Usage by Women”

Abstract: Given the wealth of literature on appearance manipulation generally, it is, perhaps, surprising that cosmetic usage receives so little empirical attention, and perhaps reflects a patriarchal approach to “appropriate” research areas. Incorporating a postfeminist approach, the current study aims to address, in part, this lacuna by providing a contemporary synopsis of the various and diverse motivations for cosmetic usage. Online, written responses to a semi-structured questionnaire were collected. In response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
(182 reference statements)
0
1
0
2
Order By: Relevance
“…The most important attitude component for using cosmetics is to be attractive and be seen as attractive. Reviewing the literature, Robertson and Kingsley (2021) showed that attractiveness brings many benefits in the areas of relationships with the opposite sex, winning lawsuits, economic success, employment and career promotion, and educational opportunities. This is the reason why people use cosmetics to gain the advantage of attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The most important attitude component for using cosmetics is to be attractive and be seen as attractive. Reviewing the literature, Robertson and Kingsley (2021) showed that attractiveness brings many benefits in the areas of relationships with the opposite sex, winning lawsuits, economic success, employment and career promotion, and educational opportunities. This is the reason why people use cosmetics to gain the advantage of attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…It has the power to increase a woman's self-esteem ( Brdar et al, 1996 ; Tran et al, 2020 ), and as a consequence can improve cognitive performance ( Palumbo et al, 2017 ). In fact, makeup can serve as a type of psychological “mask” (see Robertson et al, 2021 ), which helps to reduce negative self-perception ( Korichi et al, 2008 ), and allow individuals with elevated levels of social anxiety to present a more confident and self-assured image to the public ( Miller & Cox, 1982 ; Robertson et al, 2008 ).…”
Section: Makeup As a Strategic Tool For Self-presentationmentioning
confidence: 99%
“…Mokslinėje literatūroje atskleidžiama, kad pagrindinė moterų kosmetinių priemonių, makiažo naudojimo priežastis yra grožio ir psichologinis siekis, makiažo naudojimas yra susijęs su asmeninių poreikių tenkinimu, socialiniu bendravimu. Makiažo naudojimastai socialinis elgesys, kuris padeda jaustis lygiaverčiam su kitais [8,15,16].…”
Section: Apibendrinimasunclassified
“…Motyvacija tobulinti savo išvaizdą, tiek sąmoningu, tiek pasąmoniniu lygmeniu, yra supratimas, kad taip elgiantis galima užsitikrinti reikšmingų gyvenimo pranašumų. Atlikti moksliniai tyrimai rodo, kad profesionaliai naudojama kosmetika didina patrauklumą, o amžius yra pagrindinis veiksnys, turintis įtakos požiūriui į makiažą [15,16].…”
unclassified